2021
DOI: 10.1001/jamanetworkopen.2021.24092
|View full text |Cite|
|
Sign up to set email alerts
|

The Association Between School Closures and Child Mental Health During COVID-19

Abstract: IMPORTANCE In-person schooling has been disrupted for most school-aged youth during the COVID-19 pandemic, with low-income, Black, and Hispanic populations most likely to receive fully remote instruction. Disruptions to in-person schooling may have negatively and inequitably affected children's mental health. OBJECTIVE To estimate the association between school closures and child mental health outcomes and how it varies across sociodemographic factors. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
127
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 30 publications
6
127
0
6
Order By: Relevance
“…During the pandemic, schools have been frequently closed to reduce SARS-CoV-2 transmissions 25 . However, closure of schools and daycare facilities have had a substantial impact on development, physical and mental health of children 1315, 26 . Therefore, concepts are essential to support safe and open school settings.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, schools have been frequently closed to reduce SARS-CoV-2 transmissions 25 . However, closure of schools and daycare facilities have had a substantial impact on development, physical and mental health of children 1315, 26 . Therefore, concepts are essential to support safe and open school settings.…”
Section: Discussionmentioning
confidence: 99%
“…Economical strain due to the pandemic was a key correlate of poorer mental health [30], especially in Sri Lanka due to the impact on small and medium scale enterprises where employees not only lost their income, they found it hard to repay loans resulting in severe mental health consequences [31,32]. A recent study in US (United States) investigating school closure and children's mental health wellbeing pointed out that older children with "Black and Hispanic" background and from lower income families showed more impact on mental health than "white", younger and higher-income counterparts [33].…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), school closures, and quarantines have had substantial impacts on students' health and education. 1,2,3 Clinical trials have shown severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines to be safe and efficacious for adults, adolescents, and young children. 4 However, in some areas, vaccine uptake has been low among children and adolescents, especially compared to uptake in adults.…”
Section: Introductionmentioning
confidence: 99%